PENGARUH PMK NOMOR 152 PMK.010/2019 TENTANG CUKAI HASIL TEMBAKAU TERHADAP MINAT INVESTASI MASYARAKAT - Bernardus Bagus Krisdwianto (Business Administration Department - Universitas Katolik Parahyangan, 2019)
This study aims to find the market response on the stock market to the announcement of PMK Nomor 152/PMK.010/2019 regarding Tobacco based Product Excise by using the Event Study method using abnormal return and trading volume activity indicators. The existence of PMK Nomor 152 / PMK.010 / 2019, which aims to regulate and control public tobacco consumption through an average tax increase of 21.56%. This research conducts in 5 listed companies included in the tobacco manufacturing classification. The data used are secondary consist of daily stock prices, daily stock trading volume, and a composite stock price index (JKSE) five days before, one day at the time, and five days after the event. The Paired Sampled T-Test uses to test event studies. The result indicates that only three out of five companies experienced significant negative abnormal returns during the study period, which meant that the market responded to this event as bad news. The increasing significance of the trading volume activity did not spread evenly among those five companies. It shows the formation of an efficient market in the form of half-strong information. Therefore, investors expect to diversify their portfolios to mitigate risks that involve the detriment of government regulations.